A BIBLIOMETRIC ANALYSIS OF HUMAN RESOURCE DEVELOPMENT RESEARCH: TRENDS AND RESEARCH FOCUS FROM 2010 TO 2023 - Suryana, R.E (Jurnal Administrasi Pendidikan, 2024)
This research has the main objective of uncovering trends and research focus in the context of human resource development, using a bibliometric analysis approach, during the period 2010 to 2023. The dataset used comes from the Scopus platform and includes 817 publication metadata relevant to the topic under study. By applying the keywords "human resource development" OR "HR AND Development" in the article title column, and by limiting the research time span from 2010 to 2022, this research was able to identify main trends in the field of literature. The results of the analysis draw on research trends that specifically explore the application of technology as a strategy to improve individual performance in the context of human resource development. The implications of these findings are very relevant in supporting strategic decision making, both in the academic and practical realms. Furthermore, the research focus is also directed at several key topics, such as Artificial Intelligence, Organizational Performance, Workforce, Automation, and sustainability, creating a solid foundation for an in-depth understanding of the evolution and dynamics in human resource management literature.